Immunohistochemical analysis of Nuclear Factor-kappa B (NF-κB) between follicular and plexiform ameloblastomas: A pilot study - Sivakumar, Muniapillai (J Oral Maxillofac Pathol, 2020)
BACKGROUND: Ameloblastoma among benign tumors holds a unique position by its locally destructive and invasive nature. Tumors that originate from the odontogenic apparatus or its remnants in the jaws show diverse clinical presentations, behavior and histologic patterns. The differed biological behavior behind follicular and plexiform ameloblastomas has never attained completeness because of the lack of rhythmic correlation regarding the exact mechanism. Nuclear factor-kappa B (NF-κB) pathways play a crucial role in survival, death and differentiation during physiologic and pathologic conditions. With this background, the study has been aimed to investigate the expression of NF-κB in follicular and plexiform ameloblastomas. OBJECTIVE: The objective of this study was to analyze the immunohistochemical expression pattern of NF-κB in ameloblastoma and to compare the immunohistochemical expression pattern of NF-κB among the histological types of ameloblastoma, follicular and plexiform patterns. METHODOLOGY: Total 20 ameloblastomas (10 follicular, 10 plexiform) were immunostained with antihuman NF-κB p65 mouse IgG monoclonal antibody, and the pattern of staining is statistically analyzed using Chi-square test with the level of significance (P < 0.05). RESULTS: Twelve (3 follicular, 9 plexiform) out of 20 ameloblastomas showed immunoreactivity to NF-κB p65. In ameloblastoma, only the peripheral preameloblast-like tall columnar cells showed reactivity, whereas the stellate reticulum-like cells are immunonegative. The staining pattern was membranous in the immunoreactive cells. The results were studied with the associated and inducing pathways from the literature, and a possible mechanism has been proposed. CONCLUSION: The expression pattern of NF-κB was found to be higher in plexiform ameloblastoma than follicular ameloblastoma.